The Need for Corporate Social Responsibility and Understanding How to Implement It - ŞTEFĂNESCU, Mihnea-Răzvan (Journal of Advanced Research in Management; Vol 9 No 2 (2018): JARM Volume IX Issue 2(18) Winter 2018, 2019)
To understand the importance of strategic corporate social responsibility, the work starts from the study of specific literature and trying to identify the role of these strategies in forming and consolidating sustainable businesses. Attempts will be made to come up with typologies of social responsibility strategies that will support companies in the creation and in enhancing sustainable businesses. The study of Romanian companies has highlighted the impact that corporate social responsibility has on sustainable business. Choosing to implement the most appropriate social responsibility strategies will have an important role to play in adding value to the world by creating and developing sustainable businesses.